(untitled) (Analele Universităţii Bucureşti. Limbi şi Literaturi Străine, 2025)
The story of the novel Veba Geceleri by Orhan Pamuk, published in 2021, takes place in 1901, during the third plague pandemic, on an imaginary island in the Eastern Mediterranean, which is claimed to be a part of the Ottoman Empire. The outbreak of the plague, which is brought, like many other similar scourges, by sea, triggers a crisis of epic proportions within the small island community, forcing its vital limits and causing it to assert its identity (among other things through declaring independence and breaking away from Ottoman tutelage). Orhan Pamuk calls on all the resources of the epidemic and of the collective imaginary in times of restriction (the plague brought “from outside”, the plague as a foreigner, the foreigner as a scapegoat or as a possible agent of the plague, quarantine and the opposition to quarantine, the relations between the authorities and the population, the idea of authority, its forms, implications and risks in times of social anomie, the isolation of individuals and their loneliness in an age of distress, humanitarian disaster as the germ of social implosion, etc.) in order to create a novel that nurtures the ambition to enroll, through its explicit and implicit references, the great pandemic literature of the world.